The apocalypse factory : plutonium and the making of the atomic age - Olson, Steve, 1956- (W.W. Norton & Company, 2020)
"A thrilling narrative of scientific triumph--and the unimaginable, world-ending peril it brought us. Fearing that the Germans would be the first to weaponize the atom, the United States marshaled brilliant minds and seemingly inexhaustible bodies to find a way to create a nuclear chain reaction with unimaginable explosive power. It would begin with plutonium, the first element ever manufactured by humans. In a matter of months, a city designed to produce this dangerous material arose from the desert of eastern Washington State. Plutonium powered the bomb that dropped on Nagasaki on August 9, 1945 (a target selected in almost arbitrary fashion). And the work of Glenn Seaborg, Enrico Fermi, and hundreds of thousands of others--the physicists, engineers, laborers, and support staff of the Hanford Nuclear Facility--would remain the basis of the entire US nuclear arsenal during the Cold War and into the present. With his characteristic blend of scientific clarity and human stories, Steve Olson offers this dramatic story of human achievement--and hubris--to a new generation"--